Subtitling Translation of Medical Documentaries from the Perspective of Multimodal Discourse Analysis: A Case Study of Baby Surgeons - Zhou, Anyue (Scientific Journal of Technology, 2026)
With the increasing cross-cultural dissemination of medical documentaries, their subtitling translation plays a pivotal role in promoting the popularization of professional knowledge and facilitating humanistic exchange. Grounded in the theory of multimodal discourse analysis, this study examines the subtitling translation of the medical documentary Baby Surgeons, exploring how medical information and narrative emotion are reconstructed and conveyed in translation through the synergistic interplay of visual, auditory, textual, and other multimodal semiotic resources. The research begins by outlining the core framework of multimodal discourse analysis, then proceeds to analyze representative excerpts from the documentary—including surgical scenes, doctor-patient interactions, and professional narration—to investigate how meaning is integrated across source and target languages within a multimodal context. Findings reveal that subtitling translation for medical documentaries must balance terminological accuracy, synchronization with narrative pacing, and cross-cultural adaptation of affective resonance. Through flexible application of strategies such as compensation, simplification, and explicitation, an effective equilibrium between medical scientificity and humanistic concern can be achieved. This study offers insights for the practice of medical audiovisual translation and contributes positively to the global dissemination of medical knowledge and its public comprehension.